THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND GOVERNMENT SPENDING: A CASE STUDY OF OIC COUNTRIES - Sudarsono, Heri (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This paper presents the results for testing for causal relationship between economic growth and goverment spending for OIC countries covering the time series data 1970~2006. There are usually two propositions regarding the relation between economic growth and government spending: Wagnerâs Law states that as GDP grows, the public sector tends to grow; and the Keynesian framework postulates that public expenditure causes GDP to grow. The primary strength and originality of this paper is that we used aggregate data as well as disaggregate data for Granger causality test. By testing for causality between economic growth and government spending, we find that government spending does cause economic growth in Iran, Nigeria and Tunisia, which are compatible with Keynesianâs theory. However, the economic growth does cause the increase in goverment spending in Algeria, Burkina Faso, Benin, Indonesia, Libya Malaysia, Marocco, and Saudi, which are well-suited with Wagnerâs law.